Effect of temperature on shale strength under dynamic impact loading - Yang, Guoliang; Liu, Jie; Li, Xuguang; Bi, Jingjiu (Arabian journal of geosciences, 2020)
As shale gas development heats up, so does research into the rock nature of shale. In order to explore the mechanical properties of shale under certain temperature conditions, it provides some reference for shale gas development. Using a 50-mm-diameter split Hopkinson pressure bar (SHPB), dynamic compression tests were carried out on shale specimens at a range of temperatures between 20 and 220 °C. The dynamic deformation of the shale was analyzed. The tests showed that the shale’s stress–strain curves are similar in this temperature range. According to the research results, there is a critical temperature between 20 and 220 °C in the test temperature range. Before this critical temperature, the compressive strength of shale increases with the temperature rise, and after that, it decreases with the temperature rise. However, the curves still show brittle failure. The dynamic pressure resistance strength of the specimens, a peak strain rate effect, and the sensitivity of the specimens to the strain rate effect are different at different temperatures. There is a tendency of increasing and then decreasing with the temperature rising.